A Study on Some Contributions in Generalized Cone Graphs (International Journal of Food and Nutritional Sciences, 2022)
In this research article, we presented the gracefulness of some graph classes and how to construct bigger graceful graphs from smaller ones. In this chapter, we generalize the wheel graphs, also known as cone graphs, and study its gracefulness. This graph class was first studied by Bhat-Nayak and Selvam in 2003 and not much progress has been made since then.